Reasons for lack of treatment in patients with locally advanced, unresectable or metastatic urothelial carcinoma. (2nd September 2022) - Omland, Lise H.; Joensen, Ulla N.; Toft, Birgitte G.; Lund, Cecilia M.; Lindberg, Henriette; Knudsen, Mark B.; Tolver, Anders; Suetta, Charlotte; Pappot, Helle
Abstract: Background: The proportion of patients with locally advanced, unresectable or metastatic urothelial carcinoma that do not receive systemic anticancer treatment and the reasons for lack of treatment are largely unknown. The aim of this study was to investigate the prevalence and overall survival of this patient group and reasons for omission of treatment. Material and methods: This retrospective, single-center cohort study from Rigshospitalet, Denmark included patients diagnosed with locally advanced, unresectable or metastatic urothelial carcinoma during the study period from 1 January 2010 to 31 March 2016 who did not receive systemic anticancer treatment. Patients were identified through the Danish Pathology Register and the electronic medical records. Results: 100 patients were included, representing 34% of all patients diagnosed with locally advanced, unresectable or metastatic urothelial carcinoma at Rigshospitalet during the study period. Lack of treatment was most often due to poor physical condition (59%), decreased renal function (15%), or patient preferences (14%). Median overall survival was 1.9 months (95% CI: 1.6–2.8 months). Conclusion: One in three patients diagnosed with locally advanced, unresectable or metastatic urothelial carcinoma in the pre-immunotherapy era did not receive systemic anticancer treatment. Prompt identification of advanced disease and interventions to optimize these patients for treatment are essential. Our findings underscore the compelling need for novel, better tolerated treatment regimens in this frail patient group.